2013
DOI: 10.1158/1078-0432.ccr-12-1568
|View full text |Cite
|
Sign up to set email alerts
|

Complete Regression of Metastatic Renal Cell Carcinoma by Multiple Injections of Engineered Mesenchymal Stem Cells Expressing Dodecameric TRAIL and HSV-TK

Abstract: Purpose: Durable complete remission of metastatic renal cell carcinoma (RCC) has rarely been achieved with current treatment modalities. To solve this problem, alternative therapeutic options with high efficacy and minimal side effects are strongly needed.Experimental Design: Mesenchymal stem cells (MSC) were engineered to coexpress dodecameric TRAIL and herpes simplex virus thymidine kinase (MSC/dTRAIL-TK). The antitumor effects of MSCs expressing dTRAIL (MSC/dTRAIL) or HSV-TK alone (MSC/TK) and MSC/dTRAIL-TK… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 39 publications
1
47
0
Order By: Relevance
“…In our previous study, we found that the GCV regulating suicide gene system can significantly adjust the cell cycle of breast cancer, and most of the cells arrested in the S phase [6,7]. But how the breast cancer cells react to the GCV treatment, whether the critical targets of cell cycle checkpoint and apoptosis were changed in the GCV regulating suicide gene system is still unknown.…”
Section: Discussionmentioning
confidence: 98%
“…In our previous study, we found that the GCV regulating suicide gene system can significantly adjust the cell cycle of breast cancer, and most of the cells arrested in the S phase [6,7]. But how the breast cancer cells react to the GCV treatment, whether the critical targets of cell cycle checkpoint and apoptosis were changed in the GCV regulating suicide gene system is still unknown.…”
Section: Discussionmentioning
confidence: 98%
“…For MSC transduction, a mixture of 50 multiplicity of infection of Ad and 50 µmol/L of Fe3 + was pre-incubated in SFM at room temperature for 30 minutes and then infected into MSCs for 30 minutes, as described previously. 24 In vivo bioluminescence and fluorescence imaging…”
Section: Adenovirus (Ad) Infectionmentioning
confidence: 99%
“…The transfer of toxic GCV-3-phosphate from TKexpressing cells to TK-negative bystander cells via gap junctions may enhance therapeutic potential. 15 It has been widely accepted that the success of the strategy relies on the transfer effective gene into tumor microenvironments by specific targeting vector. 16 So far, viruses and liposomes are widely used as gene therapy vectors, but they are poor in specific tumor targeting and gene transferring, thus causing the failure of cancer gene therapy and resulting in several side effects and potential toxicity.…”
mentioning
confidence: 99%